Securitization of Small Business Loans - Christopher P. Beshouri; Peter J. Nigro (Journal of Small Business Finance, 1995)
This paper assesses the potential impact of securitization in improving small businesses' access to credit. It begins by examining the nature of small business lending and the factors that make banks the primary providers of credit to small businesses. The paper then examines the conditions under which the benefits of securitization are fully realized and whether the nature of small business lending satisfies those conditions. We argue that certain characteristics of small firm finance, especially information problems and the need for ongoing monitoring, are likely to mitigate the full benefits of securitization, that is, the substantial funding cost advantages. Specifically, loan buyers will demand substantial levels of loss protection to compensate for their uncertainty over the returns on the underlying credits and to leave intact the seller's incentive to monitor properly the loans sold. Loss protection, however, will reduce or eliminate any funding cost advantages, including capital cost reductions. In the absence of lower funding costs, banks are unlikely to undertake substantial new lending to small businesses. Securitizations of small business loans could still take place, but they are likely to be undertaken for special purposes rather than as a primary funding mechanism.
Keywords: G32; L25; 650; Small Business Loans; Lending; Borrowing; Small Business; Securitization